Pseudoartrosi e perdite di sostanza periprotesiche: inquadramento nel paziente a rischio - Calori, G.M.; Mazza, E.L.; Mazzola, S.; Romanò, F.; Colombo, A.; Monzani, V.; Colombo, M. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC NON-UNIONS AND BONE DEFECTS: ALGORITHM OF TREATMENT IN PATIENTS AT RISKThe incidence of periprosthetic fractures of the femur associated with total hip and total knee arthroplasty varies indifferent studies. Overall rates have been estimated at 2 to 5%. Although infrequent, periprosthetic femoralnon-unions create a debilitating condition for the patient. To date, the literature on the surgical management offemoral periprosthetic non-unions is very limited. Preoperative assessment included history, and radiographicexamination. All patients were additionally screened for infection with preoperative laboratory studies. Treatmentstrategies were determined by the fracture characteristics, implant fixation status and bone quality. In this article, wesuggested an algorithm of treatment for periprosthetic femoral non-unions according to our clinical experience andthe analysis of the scientific literature.